Synthesis and evaluation of novel Cu-based adsorbent-containing catalysts for CO2 hydrogenation to methanol and value-added products - Rim Ismail (18192922) (2024)
In this work, sequential incipient wetness impregnation method was used to synthesize Cu/Al2O3, Cu/Na2O/Al2O3 and Cu/CaO/Al2O3 catalysts in different compositions for CO2 conversion to value-added products. Synthesized catalysts were characterized using various analytical techniques and their performances for CO2 catalytic conversion were tested in a high-pressure packed bed reactor under reaction conditions of P = 60 bars, T = 300 °C, and H2/CO2 = 3. The obtained results revealed that the type of adsorbent had a significant impact on CO2 conversion, with CaO-containing catalyst being more efficient for methanol selectivity. Increased Cu content from 10 wt% to 30 wt% with fixed CaO content of 10 wt% resulted in a small increase in CO2 conversion where the highest CO2 conversion of 16.44% and the highest methanol selectivity (17.75%) were obtained for catalyst containing 20 wt% of copper. The best performing catalyst was further promoted using 0.5 wt% Rh promoter which improved both methanol selectivity and space time yield to 23.2% and 0.08 gMeOHgcat−1h−1, respectively. The comparative high performance of the Rh-promoted catalyst was attributed to smaller metal oxide particle size with uniform dispersion, presence of effective hydrogen spill over, moderate basic sites, surface defects and presence of induced copper species. Other Information Published in: Journal of Environmental Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jece.2024.112325